Congenital thrombotic thrombocytopenic purpura with novel mutations in three unrelated turkish children. Issue 3 (30th September 2013) - Metin, Ayse; Unal, Sule; Gümrük, Fatma; Palla, Roberta; Cairo, Andrea; Underwood, Mary; Gurgey, Aytemiz
Abstract Congenital thrombotic thrombocytopenic purpura (TTP) is an inherited disease caused by mutations in the ADAMTS 13 gene and has been reported to have diverse ages of presentation, ranging from the newborn period to adulthood. Herein, we present three cases of congenital TTP who were symptomatic during childhood (neonatal period, 7 and 10 years) and were each initially given different diagnoses. Congenital TTP was later diagnosed by molecular analysis and responsiveness to fresh frozen plasma. Three novel mutations in a homozygous state were identified in these patients: c.1308G>C, c.428T>C (p.Ile143Thr) and c.1709A>G (p.Tyr570Cys). Pediatr Blood Cancer 2014;61:558–561. © 2013 Wiley Periodicals, Inc.